1962
DOI: 10.1172/jci104458
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Biochemical Site of Action of Testosterone on Protein Synthesis in the Seminal Vesicle of the Rat*

Abstract: Although the administration of testosterone clearly causes marked diminution in nitrogen excretion (3) and results in increased protein deposition in kidney, liver, muscle, carcass, and accessory sex tissue (4), the mechanisms of this protein anabolic action are unexplained. While this effect of testosterone is probably the result of an enhancement of protein synthesis, previous attempts to elucidate this action have been complicated by two factors: first, the major enzymatic steps in the synthesis of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Elution of this and development in Kochakian and Stidworthy's benzene cyclohexane system for 40 hours resolved it into 3 peaks we refer to as Proximal [1][2][3] (Fig 2). The A third fact of possible importance is that the 2 main products can theoretically be produced by single enzymatic reductions of testosterone ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 97%
“…Elution of this and development in Kochakian and Stidworthy's benzene cyclohexane system for 40 hours resolved it into 3 peaks we refer to as Proximal [1][2][3] (Fig 2). The A third fact of possible importance is that the 2 main products can theoretically be produced by single enzymatic reductions of testosterone ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 97%
“…Potential support for this hypothesis is provided by studies on RNA pro¬ duction after hormonal therapy (Gorski et al 1965), protein incorporation in the secondary sex organs (Kochakian et . 1962;Williams-Ashman et al 1963;Wilson 1962 and many others), local puromycin application into the vagina of oestrogen treated rats (Talwar 8c Segal 1963) and the direct effect of RNA on the histological picture of the ovariectomized rat uterus .…”
Section: Discussionmentioning
confidence: 99%
“…A leading theory at the time was that steroid hormones influence protein biosynthesis by controlling amino acid transport into cells (17), but I found that testosterone administration increased protein synthesis in the male urogenital tract prior to enhancement of amino acid transport, and the findings indicated that the increase in protein biosynthesis was secondary to an increase in RNA formation (18). In a subsequent study of RNA subtypes, I showed that the enhancement of protein synthesis in rat uterus by estrogen is secondary to an increase in the formation of messenger (then termed template) RNA (19).…”
Section: Steroid Hormone Actionmentioning
confidence: 99%